PENGARUH LINGKUNGAN KELUARGA DAN KREATIVITAS MENGAJAR GURU TERHADAP HASIL BELAJAR KEWIRAUSAHAAN SISWA KELAS XI ADMINISTRASI PERKANTORAN SMK NEGERI 4 KLATEN - ANITA KUMALA SARI (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2018)
ABSTRACT This research aimed to find out: 1) Whether or not there is an effect of family environment on student learning outcomes of entrepreneurship in class XI Office Administration of SMK Negeri 4 Klaten, 2) Whether or not there is an effect of teaching creativity teacher on student learning outcomes of entrepreneurship in class XI Office Administration of SMK Negeri 4 Klaten, 3) Whether or not there is an effect of family environment and teaching creativity teacher together on student learning outcomes of entrepreneuship in class XI Office Administration of SMK Negeri 4 Klaten. This study was a quantitative research with a multiple linear regression The population of research was the student in class XI Office Administration with 83 respondents being the sample. The sampling technique used was propotional random sampling. The result of reseach, it could be found the coefficient regression Ῠ = 54,145 + 0,115X1 + 0,273X2. From the result of hypothesis testing, it could be found rstatistic (0,349) > rtable (0,2159) so that the first hypothesis stating that “There is a positive relationship between family environment and student learning outcomes” was supported. From the result of hypothesis testing, it could also be found rstatistic (0,466) > rtable (0,2159) so that the second hypothesis stating that “There is a positive relationship between teaching creativity teacher and student learning outcomes” was supported. From the result of F test, it could be seen family environment and teaching creativity teacher variables simultaneously affected the student learning outcomes with Fstatistic value = 12,521 and a= 0,05. Keywords: Family Environment, Teaching Creativity Teacher, Student Learning Outcomes